(Ne)vidne spremembe podeželskih skupnosti - Logar, Erik (Geografski vestnik, 2016)
Socioeconomic development has changed the rural community as a social and symbolic construct, and a unit of space as well. This paper discusses six changing vital, rural communities from the social perspective and cooperation. Three case studies surveyed are in Gorenjska region (Slovenia) and three in Sauerland (Germany) throughout the agrarian, industrial and information period. Comparative analysis is based on quantitative and qualitative methods that enabled us to observe (in)visible changes inside selected rural communities. We employed tangible (migration, geography) and intangible indicators (possibility of choice, increased heterogeneity). Geographical analysis of changing rural communities pointed out their increased mobility, bifurcation, co-existence of tradition, alternatives and novelties within formal and informal settings.
Keywords: agrarna geografija; Germany; Gorenjska; Nemčija; podeželje; rural area; Sauerland; Slovenia; Slovenija; Upper Carniola